Social Media Marketing Activities in Enhancing Brand Image and Driving Consumer Purchase Decisions in the Fashion Industry - M. Rifqy Roosdhani; Samsul Arifin; Nurul Komaryatin; Ali Ali; Nurul Huda; Muhammad Khoiruddin; Chenly Loing (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study investigates the role of Social Media Marketing Activities (SMMA) in influencing purchase decisions, with purchase intention as a mediating variable and brand image as a moderating variable, focusing on Sweet Mango, a local fashion brand in Jepara, Indonesia. Using a quantitative approach, data were collected from 97 respondents through online surveys and interviews, employing a purposive non-probability sampling method. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results reveal that SMMA significantly enhances purchase intention, which in turn strongly influences purchase decisions. Furthermore, purchase intention mediates the relationship between SMMA and purchase decisions. While brand image does not directly affect purchase intention, it plays a significant moderating role by strengthening the relationship between SMMA and purchase intention. Additionally, SMMA indirectly impacts purchase decisions through its influence on purchase intention. These findings underscore the critical importance of leveraging social media marketing strategies to drive consumer behavior while simultaneously building a strong brand image to maximize effectiveness. The study contributes to the literature by addressing inconsistencies in the relationship between brand image and consumer behavior and offers practical insights for local businesses aiming to optimize their digital marketing efforts. Limitations include the small sample size and focus on a single brand, suggesting opportunities for broader future research.